Geographic variation in osteoarthritis prevalence in Alberta: A spatial analysis approach. (February 2019) - Marshall, Deborah A.; Liu, Xiaoxiao; Shahid, Rizwan; Bertazzon, Stefania; Seidel, Judy E.; Patel, Alka B.; Nasr, Mina; Barber, Claire E.H.; McDonald, Terrence; Sharma, Rajrishi; Briggs, Tom; Faris, Peter; et al.
Abstract: There is limited evidence on the geographic distribution of osteoarthritis (OA) in Alberta to inform planning of equitable access to health care services. This research aimed to explore the geographic variation in age-sex standardized OA prevalence rates by geographic areas across the rural-urban continuum, and by six-digit postal codes using global Moran's I and hot spot analysis. The results demonstrated a substantially higher OA prevalence rate in Rural Remote (134.7 cases per 1000 population) and Rural (128.5), compared to Metro (107.4) and Urban areas (107.3). Metro-Edmonton had a substantially higher OA prevalence rate (124.4) compared to Metro-Calgary (94.4). OA hot spots were identified in north rural communities and Metro-Edmonton. These variations should be considered when planning programs for health promotion and prevention of osteoarthritis and access to associated health care services. Further research is needed to identify the underlying factors contributing to this geographic variation. Highlights: Explores the geographic variation in OA prevalence in Alberta with spatial analytical approach. Substantially higher OA prevalence rates in Rural and Rural Remote compared to Metro and Urban areas. Substantially higher OA prevalence rates in Metro-Edmonton compared to Metro-Calgary. Identified OA hot spots in north rural communities and Metro-Edmonton. Further research is needed to identify factors contributing to this geographic variation in OA prevalence.